Renal Denervation Prevents Immune Cell Activation and Renal Inflammation in Angiotensin II–Induced Hypertension. Issue 6 (28th August 2015) - Xiao, Liang; Kirabo, Annet; Wu, Jing; Saleh, Mohamed A.; Zhu, Linjue; Wang, Feng; Takahashi, Takamune; Loperena, Roxana; Foss, Jason D.; Mernaugh, Raymond L.; Chen, Wei; Roberts, Jackson; et al.
<x xml:space="preserve">Abstract</x> Rationale: Inflammation and adaptive immunity play a crucial role in the development of hypertension. Angiotensin II and probably other hypertensive stimuli activate the central nervous system and promote T-cell activation and end-organ damage in peripheral tissues. Objective: To determine if renal sympathetic nerves mediate renal inflammation and T-cell activation in hypertension. Methods and Results: Bilateral renal denervation using phenol application to the renal arteries reduced renal norepinephrine levels and blunted angiotensin II–induced hypertension. Bilateral renal denervation also reduced inflammation, as reflected by decreased accumulation of total leukocytes, T cells, and both CD4+ and CD8+ T cells in the kidney. This was associated with a marked reduction in renal fibrosis, albuminuria, and nephrinuria. Unilateral renal denervation, which partly attenuated blood pressure, only reduced inflammation in the denervated kidney, suggesting that this effect is pressure independent. Angiotensin II also increased immunogenic isoketal-protein adducts in renal dendritic cells (DCs) and increased surface expression of costimulation markers and production of interleukin (IL)-1α, IL-1β, and IL-6 from splenic DCs. Norepinephrine also dose dependently stimulated isoketal formation in cultured DCs. Adoptive transfer of splenic DCs from angiotensin II–treated mice primed T-cell activation and hypertension in recipient mice. Renal denervation prevented these effects of hypertension on DCs. In contrast to these beneficial effects of ablating all renal nerves, renal afferent disruption with capsaicin had no effect on blood pressure or renal inflammation. Conclusions: Renal sympathetic nerves contribute to DC activation, subsequent T-cell infiltration and end-organ damage in the kidney in the development of hypertension.